Developmentally appropriate New Media Literacies: Supporting cultural competencies and social skills in early childhood education. (June 2013) - Alper, Meryl
Young children explore their world through manipulatives, playing with 'technology' that may or may not be digital. To this end, I offer an exploration into how the existing framework of the New Media Literacies (NMLs) paradigm set forth by Henry Jenkins (2006) in Confronting the Challenges of Participatory Culture: Media Education for the 21st Century might be applicable to early childhood education. For the purposes of this paper, I focus on three of the twelve NML skills ( play, distributed cognition and transmedia navigation ) and how they might each be reflected in the interplay between digital and non-digital media within Reggio Emilia-inspired teaching and learning. Aligning the discussion of young children's media use with NMLs might allow for greater examination of the potential positive benefits of digital and non-digital media and technology.